TECHNIQUES EVALUATION - COMLEXITY CONDITION IN TECHNICAL SUBJECTS TEACHING - KROPAC, Jiri; PLISCHKE, Jitka (Journal of Technology and Information Education, 2010)
The encorporation of techniques evaluation into the technical subjects teaching represents the complexity condition for their teaching. The term ´complexity´ represents completeness, which means that through educational results the education fulfills its role in full. The complexity is associated with the integration of educational results. The article elaborates main approaches to the encorporation of techniques evaluation into the technical subjects teaching. The problematics is demonstrated on the example of the instruction aimed at the municipal waste combustion.
Keywords: complexity condition for teaching; technical subjects; techniques evaluation; municipal waste combustion